Emotional Atmosphere’s Role on People’s Application of Their Emotional Intelligence in the Fight Against COVID-19 - Nyamai, Dinah Katindi (Frontiers in Sociology, 2022)
Emotional intelligence has been associated not only with young people’s academic achievement but also with their ability to deal with harmful emotional states such as anxiety and stress. Limited research, however, has focused on influences of the emotional atmosphere on young people’s application of their emotional intelligence. This article seeks to provoke debates about the role played by accidental lessons arising from learning institutions emotional atmosphere on young people’s ability to apply their emotional intelligence in the fight against life crises such as COVID-19. The target population was 617 young people, aged 15–35 years, and the researcher used Yamane’s sample calculation formula in determining the sample size, which was 243. The researcher used two main data collection tools: a closed-ended questionnaire with 14 items and an interview guide with 10 open-ended questions. The validity of the 14-item questionnaire was determined by experts, whereas its reliability was determined using Cronbach α, which gave a reliability coefficient of 0.91. The clarity of the interview guide items was determined by two research experts. The results of both quantitative and qualitative indicated that conducive emotional atmospheres increase people’s mastery of their feelings as well as spur one’s capacity to endure discomforts associated with crises. The implication here is that we ignore the power welded by accidental lessons arising from emotional atmosphere at our peril.